Potency of Antimicrobial, Antioxidant and Cytotoxic Activities from Fractions Streptomyces MA02 - Afghani Jayuska,Puji Ardiningsih,Tika Mabella and Risa Nofiani (Journal of Applied Pharmaceutical Science, 2013)
Streptomyces sp. MA02 is potential to produce various biological activities. In previous research, its extract shows antimicrobial activities. In this study, extract prepared from Streptomyces sp. MA02 stored at -80 oC was re-evaluated the antimicrobial activity on various medium and incubation time to find out storage effect toward the antimicrobial activity. We also evaluated n-hexane and ethyl acetic fractions toward the antimicrobial, antioxidant and toxicity activities. The extract Streptomyces sp. MA02 still inhibit tested microorganisms eventhough it decreases 50% than the extract prepared from Streptomyces sp. MA02 without -80 oC storage. Antimicrobial activity was only exhibited by the methanolic fraction Streptomyces sp. MA02. The methanolic and n-hexane fractions showed cytotoxic eventhough it was not for antioxidant activity in the linoleic acid system with ferrothiocyanate reagent (FTC).
Keywords: Streptomyces sp. MA02, antimicrob